KAPABILITAS BADAN PENGAWAS PEMILU PADA PEMILU TAHUN 2019 DI KOTA PEKANBARU - Zukrina Isnaini; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Constitution Number 7 of 2017 About Election General explain that Body Supervisor Election General ( Bawaslu ) as wrong one organizer elections have role urgent in succeed election common ones that walk smooth, orderly, and quality. During maintenance Elections simultaneously 2019 a lot happening violation administration related deficiency letter voice and infringing APKs, ASN neutrality as well as political unfinished money maximized in supervision and the prosecution.As for destination from study this is for describe capability Body Supervisor Election Public ( Bawaslu ) Pekanbaru City in title election general simultaneously year 2019. The theory used in study this is Ability Organization Public according to Kusumasari which has 4 variables, consists of from capability institutional, capability source power human, capability finance ( budget ), and capability technical implementation. Study this use approach qualitative with method descriptive in data collection, writer use technique interview and documentation.Results from study this find that Body Supervisor Election Public ( Bawaslu ) Pekanbaru City in capability institutional has operate Duty as should be However weak existing rules result in the difficulty pursue legal proceedings to the violation that occurred. Lack of Source Power Man when do supervision in the field , the minimum budget supervision result in the delay supervision in the field, personally technical limitations time in handling violation make many discontinued case because has pass limit time handling violation . Keywords : Capability , Bawaslu , Election